Fit into College II: Physical Activity and Nutrition Behavior Effectiveness and Programming Recommendations. Issue 1 (April 2013) - King, Kristi McClary; Ling, Jiying; Ridner, Lee; Jacks, Dean; Newton, Karen S.; Topp, Robert
Purpose: To determine whether residency (living on campus versus off campus) was related to the effects of Fit into College on students' health behaviors, and to understand interns' perceptions of their roles in mentoring their trainees. Design: Pre-experimental, one-group, pretest-posttest design and a posttest focus group interview. Setting: University-offered health and internship courses. Subjects: Twenty-four students (trainees) participated in the intervention, nine of whom lived on campus. Five student-interns served as their mentors. Intervention: Fit into College was a 14-week intervention in which trainees teamed up with an intern to improve and/or maintain healthy nutrition and physical activity behaviors. Measures: Trainees' nutrition and physical activity behaviors and perceptions were quantitatively assessed through surveys at preintervention and postintervention. Interns' mentoring perceptions were qualitatively assessed through a focus group interview after the intervention. Analysis: Two-factor repeated measure ANOVAs and qualitative theme identification. Results: Regardless of their residency location, the trainees' perceptions of the health benefits of eating fruits and vegetables improved during the intervention. However, for trainees living on campus, the intervention was not effective in increasing the number of fruits and vegetables consumed or the planning for food preparation. The interns perceived that they did not have adequate access to healthy foods, the knowledge or skills to prepare healthy foods, or the competency to teach food preparation strategies to their trainees. For trainees living on campus, the intervention was more effective in decreasing perceived exercise barriers than trainees living off campus. Conclusion: Future iterations of Fit into College may focus on 1) improving college students' planning and preparation of healthy foods, 2) segmenting trainees into more homogeneous groups for the interns to tailor their areas of expertise (campus vs. off-campus and/or freshman vs. upperclass students), and 3) collaborating with university-partners to improve environmental conditions to promote physical activity and healthy nutrition.